Cestovní ruch na Pardubicku z hlediska programů regionálního rozvoje - Becková, Helena (Univerzita Pardubice, 2001)
Present comparatively unfavourable development of the travel industry in the regions og the Czech Republic has been caused among ohters by the fact, that general regional conceptions of travel industry development have not existed up to this time. With forming them it is necessary to take into account the basic conceptual documents concerning regional develepment in the Czech Republic. Above all the Stratehy of Regional Development of the Czech Republic and also the Regional Development Plan for Years 2000 - 2006 must be taken into consideration. The article deals with the regional parts of these documents, whose component the Pardubice district is, and defines travel industry development in this area from the standpoint of major territorial units. Finally, in connectin with int the article focuses also on tourist marketing regions, created by the Czech Tourist Authority, and characteristizes the region of Eastern Bohemia, to which the district of Pardubice belongs.
Keywords: Cestovní ruch; Regionální rozvoj; Pardubicko